Four sisters : the lost lives of the Romanov grand duchesses - Rappaport, Helen (London: Macmillan, 2014)
On 17 July 1918, four young women walked down twenty-three steps into the cellar of a house in Ekaterinburg. The eldest was twenty-two, the youngest only seventeen. Together with their parents and their thirteen-year-old brother, they were all brutally murdered. Their crime: to be the daughters of the last Tsar and Tsaritsa of All the Russias. Much has been written about Nicholas II, his wife Alexandra and their tragic fate, as it has about the Russian Revolutions of 1917, but little attention has been paid to the Romanov princesses, who - perhaps inevitably - have been seen as minor players in the drama. In Four Sisters, however, acclaimed biographer Helen Rappaport, puts them centre stage and offers readers the most authoritative account yet of the Grand Duchesses Olga, Tatiana, Maria and Anastasia. Drawing on their own letters and diaries and other hitherto unexamined primary sources, she paints a vivid picture of their lives in the dying days of the Romanov dynasty. We see, almost for the first time, their journey from a childhood of enormous privilege, throughout which they led a very sheltered and largely simple life, to young womanhood - their first romantic crushes, their hopes and dreams, the difficulty of coping with a mother who was a chronic invalid and a haeomophiliac brother, and, latterly, the trauma of the revolution and its terrible consequences.
Machine generated contents note: One.Mother Love -- Two.La Petite Duchesse -- Three.My God! What a Disappointment! A Fourth Girl! -- Four.The Hope of Russia -- Five.The Big Pair and The Little Pair -- Six.The Shtandart -- Seven.Our Friend -- Eight.Royal Cousins -- Nine.In St Petersburg We Work, But at Livadia We Live -- Ten.Cupid by the Thrones -- Eleven.The Little One Will Not Die -- Twelve.Lord Send Happiness to Him, My Beloved One -- Thirteen.God Save the Tsar! -- Fourteen.Sisters of Mercy -- Fifteen.We Cannot Drop Our Work in the Hospitals -- Sixteen.The Outside Life -- Seventeen.Terrible Things Are Going on in St Petersburg -- Eighteen.Goodbye. Don't Forget Me -- Nineteen.On Freedom Street -- Twenty.Thank God We Are Still in Russia and All Together -- Twenty-one.They Knew It Was the End When I Was With Them -- Twenty-two.Prisoners of the Ural Regional Soviet.
Includes bibliographical references and index.
Keywords: Olʹga Nikolaevna, -- Grand Duchess, daughter of Nicholas II, Emperor of Russia, -- 1895-1918.; c; c; c; Nicholas -- Emperor of Russia -- II, -- 1868-1918 -- Family; Romanov, House of; Nobility -- Russia -- Biography; Russia -- History -- Nicholas II, 1894-1917.